Plant nutrient contents of cattle manures from small-scale farms and experimental stations in the Ethiopian highlands - Lupwayi, N.Z.; Girma, M.; Haque, I. (Elsevier, 2000)
In most small-scale farms in sub-Saharan Africa, net negative balances of nutrients result when nutrients are removed from the farm by harvested crops, because farmers cannot afford inorganic fertilizers. A key resource that could be useful in reversing this trends is manure from livestock. The N, P, K, Ca, Mg, Fe, Mn, Cu and Zn contents of manures collected from six experimental stations and twenty small-scale farms in the Ethiopian highlands were analysed. The manures contained, on average 21.3 g K, 18.3 g N, 16.4 g Ca, 5.6 g Mg, 4.5 g P, 10776 mg Fe, 777 mg Mn, 92 mg Zn and 24 mg Cu per Kg. Manures from experimental stations contained significantly more N, P, K, Mg, Cu and Zn than the manures from smallholder farms, probably due to differences in feed availability and quality. Fresh manures and stored (dry) manures were not significantly different in nutrient concentrations although stored manures had slightly higher nutrient concentrations, probably as a concentration effect after loss of carbon. Manures collected in Ginchi area, but, due to scarcity of fuel wood, farmers in Deneba use manures for fuel for domestic cooking and heating instead of applying it to the soil. Afforestation programmes, or other programmes that would ease the energy problem for domestic use, may be necessary if manures are to be applied to soils. Whether the amount of manure in the livestock-dense Ethiopian highlands is sufficient to support crop production is unknown. Research in other parts of Africa indicates that, although adequate manure may be applied to some fields, insufficient manure is available to support crop production at a wider scale.